Cost comparison for construction of house using conventional and interlocking block method - Siti Aishah, Mat Ali (2012)
The population growth in Malaysia has contributed to the increasing number of construction industry for building and residential area. However, the rising price for building materials has influence the rising price of housing. This issue has affected the small construction industries in Malaysia especially in housing construction. Thus, many developers and parties are trying to find ways to construct affordable houses with shortest time. However, most of them are not aware about new method of construction which is interlocking block method. By using this method, many problems can be overcome especially the duration of construction and offers good solution in construction of affordable housing. The aim of this project is to make a feasibility study on interlocking block building system as an alternative to conventional building system for affordable housing. A sample of single storay house was chosen to calculate the cost of project which is applies conventional and interlocking block method. The difference in cost is compared using bill of quantity calculation and questionnaire method. Briefly, the results show that from survey, interlocking block system help to reduce cost and can be save up to 11.36% and 2.6% from bill of quantity calculation method. From these findings, interlocking block building system can overcome the wastage of formwork problem and reduce the number of skilled labor. Indirectly the cost of construction can be reduced.